ANALISIS STRATEGI PENGEMBANGAN USAHA UMKM KEDAI KOPI IBOE MENGGUNAKAN GENERAL MATRIX - Dea Novita Sari; Nurma Febi Ari Santi; Yoiz Shofwa Shafrani (CV. Denasya Smart Publisher, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting economic growth and creating employment opportunities. However, the development of MSMEs often faces various challenges, especially in determining appropriate business strategies to compete in an increasingly competitive market. Therefore, a strategic analysis is needed to determine the position and development strategy of a business. This study aims to analyze the business strategy of Kedai Kopi Iboe using the General Electric (GE) Matrix approach. This research uses a descriptive qualitative method with data collected through observation and literature study. The analysis was conducted by assessing two main dimensions, namely industry attractiveness and business strength. The results show that Kedai Kopi Iboe has a high industry attractiveness score and strong business capability. Based on the General Matrix analysis, the position of Kedai Kopi Iboe is in the Grow and Build quadrant. This position indicates that the business has significant opportunities for growth and development. Therefore, the strategies that can be implemented include market penetration, product innovation, strengthening digital promotion, and expanding cooperation with local communities.